EFISIENSI PEMASARAN BUNGA HORTENSIA DI DESA TULUNGREJO, KECAMATAN BUMIAJI BATU JAWA TIMUR - administrator, administrator; Wahyuningsih, Tri; Humaidi, Faisol Humaidi (Jurnal Agribisnis Wijaya Putra Surabaya, 2023)
Hortensia is a flower that has good business prospects in Batu. The price of hortensia tendsto fluctuate and the marketing margin is quite large, causing the value of the farmer's share to berelatively small. Research on the efficiency analysis of hydrangea marketing carried out inTulungrejo Village aims to identify an efficient marketing system in terms of marketing operationalefficiency. The marketing analysis approach used is qualitative and quantitative analysis. Thedetermination of farmer respondents was selected by purposive sampling as many as 20 peopleand respondents from marketing institutions using the snowball sampling method. The resultsshowed that there were 4 marketing channels formed with different channels, institutions,functions, and market behavior in each channel. Based on the analysis of marketing operationalefficiency, namely the calculation of marketing margins, farmer's share, and the ratio of profit tocost, it shows that channel IV (farmers → wholesalers → consumers) is a relatively more efficientchannel.